Successful treatment of ventriculitis due to multidrug resistant Acinetobacter baumanii with intravenous and intraventricular colistin - Ramírez-Palomino, Víctor A. (2021)
Central nervous system infections associated with devices such as external ventricular drains are frequent. Ventriculitis due to multi drug resistant (MDR) Gram-negative bacteria represent a surgical and medical challenge. We present the case of a patient who presented with intraventricular hemorrhage due to a rupture of an arteriovenous malformation that needed the insertion of an external ventricular drainage. The patient subsequently developed ventriculitis due to a MDR Acinetobacter baumanii confirmed by isolation from the cerebral spinal fluid (CSF) hat was treated based on the drug susceptibility test with intravenous and intraventricular colistin plus meropenem achieving normalization of the CSF parameters. We report the clinical evolution, complications and medical-surgical treatment in the intensive care unit.